The Legal Presumption of "Unexplained Wealth"; A Comparative Study of English and Iranian Law - seyyede omolbanin Hoseini (پژوهش تطبیقی حقوق اسلام و غرب, 2023)
The study examines a relatively novel legal presumption called "Unexplained Wealth Orders" (UWRs). According to this legal rebuttable presumption that is accepted in some countries, including England, a person is required by court order to explain about the legal origin of his wealth and assets- which is considered as extraordinary wealth, with regard to his/her known and legal income; otherwise, it is assumed that these properties and assets are illegal and must be restituted. The study argues for the adoption and development of this assumption in the Iranian legal system through a descriptive-analytical design, citing the laws and judicial procedures of the Iranian legal system, as well as examining some Hadīths. Findings, with regard specifically to the jurisprudence of Special Courts of Article 49 of the Iranian Constitution, suggest that accepting such assumption could be one of the effective steps in fighting financial corruption.